Managing Supply Chains Using Business Intelligence - Mathrani, SK (Australasian Conference on Information Systems, 2014)
Organizations are deploying business intelligence (BI) systems to enable analysis of data assets for establishing management decisions. Corporate data captured using enterprise systems (ESs) are leveraged through BI to evaluate digital information for deploying business strategies. This study investigates use of BI in organizations for managing supply chain operations. The current BI practices of manufacturing firms are evaluated for transforming transactional data captured through ESs into organizational knowledge in pursuit of realizing supply chain goals. Findings from a case study reveals that although manufacturing firms have identified business analytic as one of the major necessities for organizational effectiveness, these companies often lack clarity in aligning key measurable against their business processes to utilize vital ES data. This results in underutilization of BI tools and the data assets for establishing business decisions. However, more and more companies are now deploying BI strategies for impromptu decision making in managing supply chains.
Keywords: Business intelligence (BI), enterprise system (ES), supply chain management (SCM)